2021
DOI: 10.3390/v13040694
|View full text |Cite
|
Sign up to set email alerts
|

New World Cactaceae Plants Harbor Diverse Geminiviruses

Abstract: The family Cactaceae comprises a diverse group of typically succulent plants that are native to the American continent but have been introduced to nearly all other continents, predominantly for ornamental purposes. Despite their economic, cultural, and ecological importance, very little research has been conducted on the viral community that infects them. We previously identified a highly divergent geminivirus that is the first known to infect cacti. Recent research efforts in non-cultivated and asymptomatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The family Cactaceae includes a wide variety of succulent plants that are native to the American continent but have been introduced to almost all other continents, mainly for ornamental purposes (Fontenele et al, 2021). Several cactus species, including Trichocereus pachanoi (San Pedro cactus) and Lophophora williamsii (peyote cactus), contain a hallucinogenic alkaloid called mescaline (b-3,4,5-trimethoxyphenethylamine) (Ghansah et al, 1993;Halpern, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The family Cactaceae includes a wide variety of succulent plants that are native to the American continent but have been introduced to almost all other continents, mainly for ornamental purposes (Fontenele et al, 2021). Several cactus species, including Trichocereus pachanoi (San Pedro cactus) and Lophophora williamsii (peyote cactus), contain a hallucinogenic alkaloid called mescaline (b-3,4,5-trimethoxyphenethylamine) (Ghansah et al, 1993;Halpern, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The amplicons obtained corresponded to two sequences of ~1.8 kb. One sequence was 1852 nt in size, having only one large open reading frame (ORF) encoding a putative protein of 350 amino acids with highest amino acid sequence identity of 51.5 % to the replication-associated protein (Rep) encoded by the geminivirus, Opuntia virus 2 [20] (, Data S1). The second sequence had 1862 nt and one large ORF encoding a 323 amino acid protein with the highest amino acid sequence identity of 30.5 % to the capsid protein (CP) of the geminivirus Exomis microphylla-associated virus [21] (, Data S1).…”
Section: Resultsmentioning
confidence: 99%
“…The amplicons obtained corresponded to two sequences of ~1.8 kb. One sequence was 1852 nt in size, having only one large open reading frame (ORF) encoding a putative protein of 350 amino acids with highest amino acid sequence identity of 51.5 % to the replication-associated protein (Rep) encoded by the geminivirus, Opuntia virus 2 [20] (Fig. 1, Data S1).…”
Section: Sequence Analysis Of Geminivirus-like Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nomia bees collected as part of this study were found nesting in an urban area with the closet farms being ~3 km away; therefore, although this virus is infecting some plant species within the area, further studies are needed to determine if it is infecting cultivated or non-cultivated plants. Although no mastreviruses have been previously found in Arizona, diverse geminiviruses infecting cacti have been found [ 75 , 76 ]. Nomiamastrel virus is one of the few mastreviruses/mastrevirus-like sequences to be identified in the Americas.…”
Section: Discussionmentioning
confidence: 99%